Dynamic operation and modelling of amine-based CO2 capture at pilot scale. (December 2018) - Bui, Mai; Tait, Paul; Lucquiaud, Mathieu; Mac Dowell, Niall
Highlights: Dynamic modelling of amine-based CO2 capture pilot plant. Dynamic operation of pilot plant demonstrated. Flexible operation scenarios developed, and implemented. Successful decoupling of CO2 capture and regeneration. Abstract: This study combines pilot plant experiments and dynamic modelling to gain insight into the interaction between key process parameters in producing the dynamic response of an amine-based CO2 capture process. Three dynamic scenarios from the UKCCSRC PACT pilot plant are presented: (i) partial load stripping, (ii) capture plant ramping, and (iii) reboiler decoupling. These scenarios are representative of realistic flexible operation of non-baseload CCS power stations. Experimental plant data was used to validate a dynamic model developed in gCCS. In the capture plant ramping scenario, increased liquid-to-gas (L/G) ratio resulted in higher CO2 capture rate. The partial load stripping scenario demonstrated that the hot water flow directly affects reboiler temperature, which in turn, has an impact on the solvent lean loading and CO2 capture rate. The reboiler decoupling scenario demonstrates a similar relationship. Turning off the heat supply to the reboiler leads to a gradual decline in reboiler temperature, which increases solvent lean loading and reduces CO2 capture rate. The absorber column temperature profile is influenced by the degree of CO2 capture. For scenarios that result in lower solvent lean loading, the absorber temperature profile shifts to higher temperature (due to the higher CO2 capture rate).